An Anatomical Study on Dominant Vascular Pedicle of Tibialis Anterior Muscle and Its Implication on Tibialis Anterior Muscle Flap - Venkatesh M.S; Shwetha B.M; Manjunath K.N; Ashwini Shivaprasad; Veena Vidyashankar; Anupama K. (Indian Journal of Plastic Surgery)
Background The tibialis anterior muscle flap (TAMF) is a reliable option to provide coverage for the middle third of the leg. Identification of multiple segmental vessels for the TAMF often proves to be a tedious procedure. A single dominant vascular pedicle, if identified, can be consistently used for harvesting the TAMF. There are no anatomical studies in the literature that propose to identify the main vascular pedicle of the tibialis anterior muscle, which can be consistently used for transfer.